miR-431 promotes differentiation and regeneration of old skeletal muscle by targeting Smad4 - Lee, Kwang-Pyo (Genes Dev, 2015)
The myogenic capacity of myoblasts decreases in skeletal muscle with age. In addition to environmental factors, intrinsic factors are important for maintaining the regenerative potential of muscle progenitor cells, but their identities are largely unknown. Here, comparative analysis of microRNA (miRNA) expression profiles in young and old myoblasts uncovered miR-431 as a novel miRNA showing markedly reduced abundance in aged myoblasts. Importantly, elevating miR-431 improved the myogenic capacity of old myoblasts, while inhibiting endogenous miR-431 lowered myogenesis. Bioinformatic and biochemical analyses revealed that miR-431 directly interacted with the 3′ untranslated region (UTR) of Smad4 mRNA, which encodes one of the downstream effectors of TGF-β signaling. In keeping with the low levels of miR-431 in old myoblasts, SMAD4 levels increased in this myoblast population. Interestingly, in an in vivo model of muscle regeneration following cardiotoxin injury, ectopic miR-431 injection greatly improved muscle regeneration and reduced SMAD4 levels. Consistent with the finding that the mouse miR-431 seed sequence in the Smad4 3′ UTR is conserved in the human SMAD4 3′ UTR, inhibition of miR-431 also repressed the myogenic capacity of human skeletal myoblasts. Taken together, our results suggest that the age-associated miR-431 plays a key role in maintaining the myogenic ability of skeletal muscle with age.